2015
DOI: 10.14260/jemds/2015/1383
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Effects of Pretreatment With Magnesium Sulphate and Propofol Induction on Serum Creatine Phosphokinase and Urinary Myoglobin Levels Associated With the Use of Succinylcholine

Abstract: Succinyl Choline possess unique properties of rapid onset and short duration of action to facilitate endo tracheal intubation but myalgias, hyperkalemia, increase in serum myoglobin, creatine phosphokinase and masseter spasm are adverse effects associated with its use in apparently healthy population. The aim of present study is to compare the effects of with and without pretreatment with magnesium sulphate and propofol induction on serum creatine phosphokinase and urinary myoglobin levels associated with use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Abraham, and his colleagues (18), did not find any statistically significant changes in the levels of K+ and CK when using rocuronium prior to the injection of succinylcholine. Another research detected the CK levels after using succinylcholine and reported that the average postoperative increase in the study groups was statistically significant (23). Other investigators notified a significant increase in K+ and CK levels following succinylcholine administration (9).…”
Section: Discussionmentioning
confidence: 99%
“…Abraham, and his colleagues (18), did not find any statistically significant changes in the levels of K+ and CK when using rocuronium prior to the injection of succinylcholine. Another research detected the CK levels after using succinylcholine and reported that the average postoperative increase in the study groups was statistically significant (23). Other investigators notified a significant increase in K+ and CK levels following succinylcholine administration (9).…”
Section: Discussionmentioning
confidence: 99%
“…It possesses a unique property of rapid onset and short duration of action, but is accompanied by side effects like muscular fasciculation, myalgia, masseter muscle spasm, hyperkalemia, rhabdomyolysis, increase intracranial pressure, intraocular pressure and intragastric pressure. [1] The succinylcholine induced postoperative myalgia (POM) has been shown to occur in 41% -92% of patient. [2] The pathophysiology of fasciculation and myalgia is unclear and exact mechanism of succinylcholine induced myalgia is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Succinylcholine, a depolarizing muscle relaxant was introduced in 1952 by Sleff and Foldes and has a unique place in clinical practice, because it causes quick and excellent skeletal muscle relaxation for few minutes followed by spontaneous recovery. It possesses a unique property of rapid onset and short duration of action, but is accompanied by side effects like muscular fasciculation, myalgia, masseter muscle spasm, hyperkalemia, rhabdomyolysis, increase intracranial pressure, intraocular pressure and intragastric pressure 1 . This succinylcholine induced postoperative myalgia (POM) has been shown to occur in 41%-92% of patients 2 .…”
mentioning
confidence: 99%